Mulheres profissionais pós maternidade e a manifestação das estratégias de autoliderança em suas vivências no trabalho - Maggioni, Márcia Bandeira Landerdahl (2022)
Brazilian professional women have consolidated their work in the labor market by integrating multiple roles, often combining the exercise of motherhood, in search of personal and professional fulfillment. Currently, the possibility of actively maintaining the spheres of career and personal life with children is considered essential in the female trajectory. However, in this path, obstacles remain to be overcome, including those related to the overload of responsibilities resulting from the reconciliation of professional, personal and family life, as women remain the main responsible for raising and bonding with children (LIMA; LUCAS; FISCHER, 2011; OLIVEIRA et al., 2011; ANDRADE, 2012; FRANCO, 2018; REIS et al. 2018). This leads to the present study, with the objective of analyzing how Brazilian post-maternity professional women manifest the use of self-leadership strategies, through their constitutive categories and dimensions, in their experiences at work. Thus, it was proposed to research the reality of professional women after maternity at work, recognizing the complexity of their experience, the conflicts and challenges involved in reconciling their roles, and having self-leadership as an alternative to be used by women in the process of conducting of their professional and personal lives. To this end, two studies were carried out, the first being of a quantitative nature, through the application of a survey with the RSLQ-Br self-leadership scale with 354 post-maternity Brazilian professional women, which allowed the investigation of the psychometric properties of the scale and the identification of of the categories and dimensions of self-leadership with the highest incidence among the participants. The second study, of a qualitative nature, was developed through the application of semi-structured interviews with 21 women, characterized in terms of their work and motherhood trajectories, who had the use of self-leadership strategies analyzed to understand the manifestation in their daily experiences and the role of self-leadership in their post-maternity professional trajectories. In Study 1, after the validation of the RSLQ-Br self-leadership scale for application with post-maternity professional women, a higher incidence of use of the category of strategies for natural rewards was identified, followed by the categories of strategies of constructive thought patterns and focused on behavior. In Study 2, it was possible to identify the use of the three categories of self-leadership strategies, in addition to demonstrating how women perceive their experiences in reconciling work and maternal roles. The results obtained demonstrate the daily use of self-leadership strategies by post-maternity professional women participating in their experiences at work, but the challenges and difficulties related to the reconciliation of motherhood and work remain, which indicate the need to develop public and organizational policies that allow relieve some of the pressure and burden suffered by these women. The research advances the discussion on the conciliation of motherhood and work, emphasizing the importance of using strategies that allow better results in both fields, strengthening professional women, exploring possible alternatives that allow better balance, less overload and the reduction of guilt in the division of tasks and responsibilities.